The TPRS Puzzle: Effective Storytelling in a LOTE Classroom - Lisa M. Roof; Cheryl A. Kreutter (Networks: An Online Journal for Teacher Research, 2010)
The Teaching Proficiency through Reading and Storytelling (TPRS) method promised superior results in a second language classroom. However, experiences using the method in a middle school Spanish classroom were not always positive. Classroom structure dissolved during the interactive storytelling sessions when students’ disruptive responses overshadowed the benefits of the teaching method. This paper describes an action research project designed to analyze student engagement during two different TPRS lessons. In the first lesson, the classroom teacher followed the TPRS procedures with no modifications. In the second lesson, the teacher revised the lesson procedures by (a) explicitly stating clear expectations and giving the students a concrete measurement of expectations, (b) providing an added visual element, and (c) giving the students opportunities to respond chorally during the storytelling. Students were more positively engaged for the second lesson as evidenced by their active response to the story in the target language. Results suggest that, along with providing clear expectations for the students’ role during the lesson, adding strong classroom management, story-related props and choral response are useful ways to support student learning using TPRS in a second language classroom.